Effect of Fertilizer Phosphorus Rate on Tomato and Green Bean Yield and Growth in High pH Sandy Soils of South Florida - Kelly T. Morgan; Kamal Mahmoud (EDIS)
This 4-page fact sheet addresses the effect of phosphorus rate on tomato and green bean yield and growth in high pH soils and discusses their relationship to both nutrition and fertilizer management. Written by Kelly T. Morgan and Kamal Mahmoud, and published by the UF Department of Soil and Water Science, December 2013.